Inovasi Dalam Perencanaan Pembelajaran Untuk Mendorong Keaktifan Dan Kreativitas Siswa - Sabina Khairunnisa; Fitriani Fitriani; Safran Safran (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research delves into innovative methodologies for lesson planning aimed at fostering student engagement and creativity. The study assesses the impact of these innovative approaches on students' active participation and creative thinking. The findings offer valuable insights into effective strategies for educators to cultivate a dynamic and creative learning environment. The research underscores the importance of adopting pedagogical techniques that not only capture students' attention but also stimulate their creativity throughout the learning process. The study contributes to the ongoing discourse on educational innovation, emphasizing the need for adaptable and engaging teaching methods in today's diverse classrooms. Keywords: , ,